Simply-supported multi-layered beams for energy harvesting - Patel, Rupesh; Tanaka, Yoshikazu; McWilliam, Stewart; Mutsuda, Hidemi; Popov, Atanas A. (SAGE Publications, 2017)
This paper develops an analytical model for predicting the performance of simply-supported multi-layered piezoelectric vibrating energy harvesters. The model includes the effects of material and geometric nonlinearities, as well as axial pre-tension/compression, and is validated against experimental devices for a large range of base accelerations. Numerical and experimental investigations are performed to understand the benefits of using simply supported devices compared to cantilevered devices. Comparisons are made in an unbiased manner by tuning the resonant frequency to the same value by modifying the geometry, and the results obtained indicate that simply supported devices are capable of generating higher voltage levels than cantilever devices. The model is also used to investigate the benefits of using multi-layered devices to improve power density. Depending on harvester composition, power-per-unit-volume of piezoelectric material for a device is increased through the stacking of layers.